Pengaruh Akupuktur Titik Baihui (GV20) dan Elektroakupunktur Titik Zusanli (ST36) terhadap Jumlah Leukosit Tikus Putih (Rattus norvegicus) Model Stres Akibat Bising Intermiten Kronik - fauzi, ridwan; Balgis, .; Isdaryanto, . (Nexus Biomedika, 2014)
Background: This stydy is to know the effect of acupuncture at Baihui (GV20) acupoint and electroacupuncture at Zusanli (ST36) acupoint to WBC level in stress model white rats resulting from chronic intermittent noise. Methods: This study was an experimental with pre and post test group designs. Subjects were 32 male white rats (Rattus norvegicus), wistar strain samples and grouped into 2 groups. KB (the noise group) were induced with chronic intermittent noise and KBA (acupuncture-noise group) were induced with chronic intermittent noise and treated with acupuncture at Baihui (GV 20) acupoint and electroacupuncture at Zusanli (ST36) acupoint. Subjects was treated for 28 days. The collected data were analyzed using independent samples t-test, paired-samples t-test, alternative test with Wilcoxon test, and Mann-whitney test. Results: Mean KB (pre test), KB (post test), KBA (pre test), and KBA (post test) were 12,952.50±2,845.52/uL; 8,151.88±1,978.19/uL; 12,493.13±2,584.90/uL; and 8,942.50±2,591.93/uL, respectively. The statistic analysis showed that there was a significant difference of white blood cell count between KB (pre test) and KB (post test) as well as between KBA (pre test) and KBA (post test) but there was no significant difference between KB (pre test) and KBA (pre test) as well as beetween KB (post test) and KBA (post test). Conclusion: There is no effect of acupuncture at Baihui (GV20) acupoint and electroacupuncture at Zusanli (ST36) acupoint against WBC level of white rats model stress resulting from chronic intermittent  noise. Keyword: WBC, Acupuncture and electroacupuncture, chronic intermittent noise.